PERBANDINGAN KINERJA INDUSTRI MAKANAN HALAL INDONESIA DENGAN NEGARA-NEGARA UTAMA EKONOMI ISLAM - Mustofa Mahfudz Fauzi; Danish Zulfan Al-fathan; Hikmah Dzilhijjah (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to compare the performance of Indonesia's halal food industry with that of major Islamic economic countries based on the State of the Global Islamic Economy (SGIE) Report 2024/25. Using literature review and secondary data analysis, this study positions Indonesia in the halal food sector, identifying the driving factors, and identifying obstacles to improving global competitiveness. The results show that Indonesia ranks third in the Global Islamic Economic Indicator (GIEI), but still lags behind Malaysia and Saudi Arabia in terms of exports, industrial innovation, and the strength of its halal ecosystem. This study provides strategic recommendations to strengthen Indonesia's competitiveness through strengthening halal certification, supply chain digitalization, and the development of halal industrial parks.Keywords: Halal food, SGIE 2024/25, Indonesia, Malaysia, Saudi Arabia, halal industry.